Etidronate halts systemic arterial calcification in pseudoxanthoma elasticum. (January 2020) - Bartstra, Jonas W.; de Jong, Pim A.; Kranenburg, Guido; Wolterink, Jelmer M.; Isgum, Ivana; Wijsman, Alayna; Wolf, Bas; den Harder, Annemarie M.; Mali, Willem P. Th. M.; Spiering, Wilko
Abstract: Background and aims: In pseudoxanthoma elasticum (PXE), low levels of inorganic pyrophosphate result in extensive arterial calcification. Recently, the treatment of ectopic mineralization in the PXE (TEMP) trial showed that one year of treatment with etidronate halts progression of femoral artery calcification in PXE patients. The aim of this study was to test the efficacy of etidronate on calcification in different vascular beds. Methods: In this prespecified post-hoc analysis of the TEMP trial, arterial calcification mass was quantified in the carotid siphon, common carotid artery, thoracic and abdominal aorta, coronary arteries, iliac arteries, and the femoropopliteal and crural arteries using CT at baseline and after one year of etidronate treatment or placebo. In addition, a total arterial calcification score was calculated. The difference in calcification progression was compared between the etidronate and placebo group. Results: 74 PXE patients were enrolled and randomized. Etidronate significantly halted progression of calcification in all vascular beds except for the coronary arteries. For the total arterial calcification score, the median absolute increase in mass score was −63.6 (−438.4–42.2) vs. 113.7 (9.4–377.1) ( p  < 0.01) and the median relative increase was −2.4% (−10.3–3.8) vs. 6.3% (0.2–15.8) ( p  < 0.01) in the etidronate and placebo arm, respectively. Conclusions: Etidronate treatment halts systemic arterial calcification in PXE. Further research must assess the long term safety and efficacy of etidronate on clinical outcomes in PXE. Graphical abstract: Image 1 Highlights: Pseudoxanthoma elasticum results in extensive arterial calcification. Etidronate halts systemic arterial calcification in pseudoxanthoma elasticum. Further studies must assess the efficacy of etidronate on clinical outcomes.